EVALUATION OF GOOD DISTRIBUTION PRACTICE (GDP) IMPLEMENTATION IN DRUG STORE AT MLATI, SLEMAN, YOGYAKARTA - Isna Sugih Hartini; Marchaban Marchaban (Faculty of Pharmacy, Universitas Gadjah Mada, 2016)
Drug distribution is an important process in maintaining efficacy, safety, and quality of a drug after manufacturing process. Good Distribution Practices (GDP) should be implemented in distribution facilities included pharmacies. Drug quality should be main concern until the drug is administered to patients. This study is intended to determine GDP implementation and follow-up steps that should be implemented to pharmacies in Mlati, Sleman, Yogyakarta. It is a descriptive qualitative study conducted on pharmacies by reviewing the application of GDP upon the profile aspects of facilities, buildings and equipment, procurement, reception and storage, distribution, handling of product returns and expire date, etc. Primary data obtained by interviewing head of pharmacists (APA) or vice of head pharmacists using the check-list form. Subsequently, the data are analyzed qualitatively to determine the follow-up steps which should be taken to pharmacies that are not eligible to operate. The results showed that no one of pharmacy absolutely follows the GDP rule, 88.89% of pharmacies should be warned seriously, and 11,11% of pharmacies should be suspended temporarily.